2016
DOI: 10.1007/s00395-016-0558-1
|View full text |Cite
|
Sign up to set email alerts
|

9th Hatter Biannual Meeting: position document on ischaemia/reperfusion injury, conditioning and the ten commandments of cardioprotection

Abstract: In the 30 years since the original description of ischaemic preconditioning, understanding of the pathophysiology of ischaemia/reperfusion injury and concepts of cardioprotection have been revolutionised. In the same period of time, management of patients with coronary artery disease has also been transformed: coronary artery and valve surgery are now deemed routine with generally excellent outcomes, and the management of acute coronary syndromes has seen decade on decade reductions in cardiovascular mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 79 publications
0
73
1
1
Order By: Relevance
“…As discussed in detail earlier, most of the studies performed to date are heterogeneous: use of (1) different clinical entities with different clinical protocols (CABG, CABG+valve surgery, cardiac surgery in children, STEMI, PCI), (2) different inclusion/ exclusion criteria even for the same clinical entity and protocol, (3) different conditioning algorithms, and (4) different methods to measure infarct size (troponin I, troponin T, creatine kinase-muscle brain, single photon emission computed tomography, magnetic resonance imaging) have all contributed to the current uncertainty on the efficacy of conditioning procedures in clinical practice. It is most disconcerting that there are several consensus papers that highlight these problems with the existing studies on cardioprotection and make detailed recommendations on how an ideal study should be conducted, 12,13,228,246,249 but then some of the authors of such consensus papers go on to publish studies that do not adhere to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in detail earlier, most of the studies performed to date are heterogeneous: use of (1) different clinical entities with different clinical protocols (CABG, CABG+valve surgery, cardiac surgery in children, STEMI, PCI), (2) different inclusion/ exclusion criteria even for the same clinical entity and protocol, (3) different conditioning algorithms, and (4) different methods to measure infarct size (troponin I, troponin T, creatine kinase-muscle brain, single photon emission computed tomography, magnetic resonance imaging) have all contributed to the current uncertainty on the efficacy of conditioning procedures in clinical practice. It is most disconcerting that there are several consensus papers that highlight these problems with the existing studies on cardioprotection and make detailed recommendations on how an ideal study should be conducted, 12,13,228,246,249 but then some of the authors of such consensus papers go on to publish studies that do not adhere to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The potential reasons for this discrepancy have been discussed in detail. [245][246][247][248] Importantly, both ERICCA and RIPHeart not only failed to find benefit from remote ischemic conditioning on mortality, myocardial infarction, and stroke at hospital discharge 38 or after 12 months, 37 but they also failed to see an acute benefit in terms of a reduction of troponin release, such that from the lack of an acute protection, no better clinical outcome was to be expected. The most likely reason for the failure to see protection in terms of troponin release and clinical outcome is the use of propofol anesthesia in 90% of ERICCA patients and all patients per-protocol in RIPHeart.…”
Section: Current State Of Translation For Remote Ischemic Conditioningmentioning
confidence: 99%
“…Newer strategies such as ischemic preconditioning (IPC), ischemic postconditioning, and remote IPC have been shown to condition the myocardium to IRI and thus reduce the final myocardial infarct size (7). The elucidation of underlying mechanisms in different forms of ischemic conditioning has identified novel targets for cardioprotection amenable to pharmacological manipulation, so called pharmacological conditioning (8).…”
mentioning
confidence: 99%
“…However, none has been translated into clinical practice with the exception of early reperfusion (14)(15)(16). The reasons for the failure to translate pharmacologic conditioning strategies of cardioprotective effects from the bench to bedside have been extensively discussed in the literatures (3,(8)(9)(10)(11)(14)(15)(16)(17)(18)(19). Some experts concluded that the causes of failure can be attributed to inadequacy animal IRI models used in the preclinical cardioprotection studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation